Kontroversi seputar Wacana Mushaf ‘Utsman - Hamdani Anwar (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2003)
This article aims to explore various issues surrounding the establishment of the Mushaf ‘Uthmani. This research reveals many intriguing aspects worth highlighting, from the perspectives of the Companions, scholars, and orientalists. The Mushaf ‘Uthmani, the official version of the Qur’an compiled during the caliphate of Uthman ibn Affan, has often been the subject of debate and in-depth study. The Companions of Prophet Muhammad (PBUH), who were direct witnesses to the revelation of the Qur’an, had diverse views on the compilation and writing of this mushaf. Some Companions fully supported this process, while others raised criticisms and concerns. Both classical and contemporary scholars have made significant contributions to interpreting and understanding this codification process. They explore the historical, theological, and philological aspects of the establishment of the Mushaf ‘Uthmani, influencing how Muslims view their sacred text. Additionally, Western orientalists have long been interested in studying this process from a critical and academic perspective. Their approaches often differ from traditional Islamic views, sparking dynamic discussions and debates among academics. This study not only delves into the history of the establishment of the Mushaf ‘Uthmani but also considers its implications for the development of Qur’anic studies, from both the internal perspective of Muslims and the external perspective of orientalists. Through a multidisciplinary approach, this paper offers a comprehensive understanding of the complexities and dynamics surrounding the establishment of the Mushaf ‘Uthmani, while also opening up space for further discussion in the future.